Data from: Genetic relationships of extant brown bears (Ursus arctos) and polar bears (Ursus maritimus) - Cronin, Matthew A.; MacNeil, Michael D. (Dryad Digital Repository, 2012)
Polar bears (Ursus maritimus) and brown bears (Ursus arctos) are closely related species for which extensive mitochondrial and nuclear phylogenetic genetic comparisons have been made. We used previously-published genotype data for 8 microsatellite DNA loci from 930 brown bears in 19 populations and 473 polar bears in 16 populations to compare the population genetic relationships of extant populations of the species. Genetic distances (Nei standard distance = 1.157), the proportion of private alleles (52% of alleles are not shared by the species), and Bayesian cluster analysis are consistent with morphological and life history characteristics that distinguish polar bears and brown bears as different species with little or no gene flow among extant populations. Bear microsats for Paper For Dryad ArchiveThe file contains diploid genotypes for eight microsatellite DNA locifor three species of bears that were first reported in previous publications.